Pengaruh Edukasi Media Komik Terhadap Pelaksanaan Metode Kanguru Pada Bayi Prematur Di Kota Kupang - Dafroyati, Yuliana; Kapitan, Meiyeriance; On Manimabi, Lidya Valeri (Jurnal Kesehatan Panca Bhakti Lampung, 2025)
Background: Kangaroo Method Care (FMC) is a method of early care with skin-to-skin contact between mother and newborn in a kangaroo-like position. This technique allows skin-to-skin contact between mother and baby for 24 hours, which stabilizes the baby's body temperature, calms the baby, and results in more breastfeeding, which can be done during hospitalization or at home. Objective: To determine the effect of comic media education on the implementation of the Kangaroo Method in premature infants. Methods: The research method is a quasi-experiment with two groups, namely the intervention group and the control group, the population in this study amounted to 40 respondents. The statistical test used is non-parametric with Wilcoxon Test and Mann Whitney Test. Results: There is an effect of Comic Media Education on the Implementation of the Kangaroo Method in Premature Babies in Kupang City, where it is obtained asymp.sig (2-tailed) worth 0.000 <0.05. Conclusion: There is an effect of comic media education on the knowledge and attitudes of respondents about the implementation of the kangaroo method in premature babies in Kupang City. Suggestion: It is expected that the level of knowledge and attitudes of respondents about kangaroo method treatment in premature infants who have sufficient and good categories should be improved so that respondents can see sources of information from comic media, videos, leaflets and other social media.